THE STUDENT AFFAIRS ADMINISTRATION MODEL OF NURSING EDUCATION INSTITUTIONS UNDER RAJABHAT UNIVERSITIES IN THE UPPER NORTHERN REGION - Kamdaeng, Praveeda; Boonchai, Thanat; Thumachai, Prapan; Lorga, Thaworn (Journal of Social Science and Cultural, 2025)
This research aimed to study the current conditions and ideal expectations of student affairs administration, develop and validate a student affairs administration model and its implementation manual, and evaluate the effectiveness of the model and manual for nursing education institutions under Rajabhat Universities in the upper northern region of Thailand. A mixed-methods approach was employed. The population consisted of 569 administrators, full-time faculty members, and students from these institutions in the academic year 2024. A stratified proportional sampling method was used to select 230 participants. Key informants included experts from three nursing institutions with good practices in student affairs administration, selected through purposive sampling. The research instruments comprised questionnaires, interviews, and record forms. Data collection methods involved surveys, interviews, and focus group discussions. Data were analyzed using frequency, percentage, mean, standard deviation, and content analysis. The findings indicated that both the current conditions and ideal expectations for student affairs administration were rated at a high level ( = 4.29, S.D. = 0.67); ( = 4.47, S.D. = 0.59). The essential components for effective student affairs administration include planning, organizing, leading, and controlling. The developed student affairs administration model consists of five main components: principles, objectives, systems and mechanisms, evaluation guidelines, and success conditions. The implementation manual contained five sections: instructions, introduction, principles and rationale, content and usage guidelines, and references. The evaluation of the model and manual showed that all items were rated at the highest level for feasibility and usefulness ( = 4.66, S.D. = 0.39); ( = 4.78, S.D. = 0.36); ( = 4.68, S.D. = 0.39); ( = 4.76, S.D. = 0.36) respectively, confirming their accuracy and appropriateness for nursing education institutions.